Pain thresholds are unaffected by age in a Japanese population. Issue 5 (24th February 2020) - Suzuki, Yasuhiro; Muramatsu, Ken; Maruo, Kazushi; Kato, Hidenori; Tanabe, Yuuki; Tubaki, Takumi; Hada, Yasushi
Abstract: Introduction: Assessment of sensory impairment in diabetic patients by pain threshold test using intraepidermal electrical stimulation (IES) is a recently developed technique. However, there are no normative pain thresholds in healthy people. Methods: We examined pain, vibration, and pressure thresholds in 178 healthy subjects using IES, vibration perception testing (VPT), and Semmes‐Weinstein monofilament testing (SWMT). Results: The mean values for each age group for pain threshold ranged from 0.07 to 0.12 mA. Pain thresholds were unaffected by age. As the age increased, VPT values decreased from 18.0 to 10.6 seconds and SWMT values increased from 21.4 to 45.3 g/mm 2 . There were no significant differences in pain threshold, VPT, and SWMT between men and women. Discussion: The pain threshold test appears to be useful for diabetic neuropathy screening because normative values are not affected by age.